Avian infectious bronchitis virus (AIBV) review by continent - Rafique, Saba; Jabeen, Zohra; Pervaiz, Treeza; Rashid, Farooq; Luo, Sisi; Xie, Liji; Xie, Zhixun (Frontiers in Cellular and Infection Microbiology, 2024)
Infectious bronchitis virus (IBV) is a positive-sense, single-stranded, enveloped RNA virus responsible for substantial economic losses to the poultry industry worldwide by causing a highly contagious respiratory disease. The virus can spread quickly through contact, contaminated equipment, aerosols, and personal-to-person contact. We highlight the prevalence and geographic distribution of all nine genotypes, as well as the relevant symptoms and economic impact, by extensively analyzing the current literature. Moreover, phylogenetic analysis was performed using Molecular Evolutionary Genetics Analysis (MEGA-6), which provided insights into the global molecular diversity and evolution of IBV strains. This review highlights that IBV genotype I (GI) is prevalent worldwide because sporadic cases have been found on many continents. Conversely, GII was identified as a European strain that subsequently dispersed throughout Europe and South America. GIII and GV are predominant in Australia, with very few reports from Asia. GIV, GVIII, and GIX originate from North America. GIV was found to circulate in Asia, and GVII was identified in Europe and China. Geographically, the GVI-1 lineage is thought to be restricted to Asia. This review highlights that IBV still often arises in commercial chicken flocks despite immunization and biosecurity measures because of the ongoing introduction of novel IBV variants and inadequate cross-protection provided by the presently available vaccines. Consequently, IB consistently jeopardizes the ability of the poultry industry to grow and prosper. Identifying these domains will aid in discerning the pathogenicity and prevalence of IBV genotypes, potentially enhancing disease prevention and management tactics.